Mother's Anxiety Level With Readiness Before Delivery at PMB Deli Serdang - Megawati Sinambela (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Mother's readiness before delivery should be a priority for mothers and health workers in pregnancy services, because it can lead to excessive maternal worry in the face of childbirth. The purpose of this study was to analyze the relationship between the level of maternal anxiety before delivery which took place at the Independent Midwife Practice of Deli Serdang Regency. This study is an explanatory research. The population in this study were pregnant women in the third trimester with a sample of 60 respondents. The results obtained p value = 0.001 <0.05, which means that there is a significant relationship between the level of maternal anxiety and readiness for delivery. Suggestions according to the results of the study are that it is considered necessary to provide education for pregnant women to reduce the level of maternal anxiety before childbirth. As well as motivating mothers to visit health services to get ante-natal services according to standards based on gestational age, especially before delivery, thereby reducing anxiety when facing childbirth.